Deliberating change: Conditions that shape how teachers voice and debate beliefs about instructional reforms. Issue 2 (15th April 2019) - Lockton, Marie
Abstract : Purpose: How teachers collectively address conflicting beliefs about reforms and come to privilege some over others is critically important in understanding instructional change and stability. The paper aims to discuss this issue. Design/methodology/approach: Drawing on in-depth qualitative data gathered in interviews and observations of teachers' formal collaboration time, this study focuses on teacher dialogue to examine the voicing and debate of teachers' beliefs about reform efforts in their schools. Specifically, in two urban middle schools engaged in math instructional reforms, what are the conditions of teachers' collaboration time that shape their dialogue about the feasibility of these reforms? Findings: The findings reveal that the beliefs teachers voice vary widely depending on the topic of conversation. Teachers' conversations about student achievement data and tracking elicited doubts about the possibility of instructional change, and conversations about other forms of student data and instructional strategies elicited a wider range of beliefs. Further, opportunities to meet with trusted colleagues as well as with wider groups provide teachers with different, but both useful experiences in exploring their own conflicting beliefs. Practical implications: Avenues for shifting institutionalized beliefs about instruction in schools that have struggled to embrace equitable instructional practices for struggling students are discussed, along with implications for future research. Originality/value: There is considerable research highlighting the characteristics of productive collaboration, but this paper provides a deeper understanding of the way teachers collectively negotiate beliefs about instructional changes in schools struggling to meet that mark.